(untitled) (American Journal of Islam and Society, 2009)
TheAssociation ofMuslim Social Scientists of NorthAmerica (AMSS) held its fifth annual Canadian Regional Conference in Waterloo, Ontario, at Wilfred Laurier University (WLU) on 21 May 2009. The Muslim Studies Option Program Committee and the Department of Religion and Culture at WLU cosponsored this event, and Jasmin Zine (WLU) andMeena Sharify- Funk (WLU) were the cochairs. The Tessellate Institute, a CanadianMuslim think tank, coordinated and cosponsored the keynote panel. The theme, “Nation, Citizenship, and Belonging: Muslim Cultural Politics in Canada,” brought together academics, emerging scholars, and community activists to explore critical questions about the space in the middle where engaged Muslim Canadians stand. In her opening remarks, Sharify-Funk identified that space as being located on an isthmus between the realities of abject discrimination and the potentialities of citizenship. She remarked that this conference sought to ask the difficult questions about whetherMuslim Canadians can engage the challenges and move beyond the internal contradictions that inherently shape Muslim cultural politics ...